Communicative Behavioral Competences: Proposal of an Observation Matrix for Pedagogy Students in Context of Cultural Diversity - Tapia-Vidal, Alejandra Soledad (2020)
Intercultural communicative competences have been analyzed profusely for 15 years, however, the greatest of the tools developed to evaluate have been self-reports on dimensions limited in affective and cognitive communication skills; nevertheless, the dimension on communicative behavioral competences (CCC from now on) has not received special attention, which has translated into a vacuum in the development of this area. The objective of this research is to present the reliability of an instrument that allows describing and analyzing the CCC of pedagogy practitioners in a cultural diversity context the theoretical model of Chen and Starosta (1996). For the development of the methodology, an instrument was designed through a theoretical analysis of CCC. In turn, an external reliability process was developed through expert judgment, an internal reliability analysis through the application of a matrix by interobservers and the instrument was applied in real context. The results show a good theoretical support that supports the behavioral dimensions in relation to the use of the voice, kinésica-gestualidad, proxemic and use of space. Likewise, indicators contributed by the interjueces that contributed to adjust the matrix are revealed. In this way, the generated instrument allows the researcher to observe, record descriptively, situations related to the nonverbal and paraverbal language of the participant from an ethnographic approach. Finally, the limitations and projections of the instrument were analyzed to explore this dimension as a first input and challenge to field researchers.